Optimalisasi Penguasaan Materi Garis dan Sudut Melalui Pendekatan Pembelajaran Berbasis Masalah di SMP - Suryana, Muhammad Fakhrudin (Manajemen Pendidikan, 2015)
This research surrounded by still have not optimal of domination of matter Demokrasi among student and implementation  of study approach bases on problem at class student  VIII E State Junior  High School  Three Teras Region  Boyolali  even semester  of school year 2014/2015. This research aim to description about optimalisation of domination of  matter  line  and  angle  through  study  approach  bases  on  study  internal  issue  of mathematics at class student VIII E State Junior High School Three Teras Region Boyolali. Subject   and   research   data   source   is  24  students.   Data   collecting   method   applies observation,  questionare,  documentation,  and test. Data analysis applies critical analysis and comparability. Indicator success of using minimal limit criteria 75 and complete target of class 100%. Research  procedure  applies cycle. Result of research and solution  it is by know that data obtained from finite initial condition of cycle II, obtained progress of achievement  of  student  learning  in  study  of  mathematics  with  matter  line  and  angle through approach of problem based learning, at initial condition average of 72,1 and cycle I average of 76,4 and cycle II average of 84,4. From this data, seems to explain that happened increase of average of value from initial condition to cycle I 4,3 numbers (6%), from cycle I to cycle II happened increase equal to 8 number (10,5%), from precycle to cycle II happened increase 12,3 numbers (17,1%). Highest value of initial condition phase 82 and cycle I 86 and cycle II 92. Seems  to explain  that from initial  condition  phase to cycle I happened increase equal to 4 number (4,9%), from cycle I to cycle II happened  increase equal to 6 number  (7%),  and  from  initial  condition  to  cycle  II  happened  increase  10  numbers (12,2%). Low value of initial condition phase is obtained by 66 and cycle I 70 and cycle II76. thereby, can be affirmed that from initial condition phase to cycle I happened increaseequal  to 4 number  (6%),  from cycle I to cycle II happened  increase  equal  to 6 number (8,6%),  and  from  initial  condition  to cycle  II happened  increase  10 numbers  (15,2%). Complete  percentage  learnt starts from initial condition  is obtained  equal to 27,3% and cycle I is obtained equal to 54,5% and cycle II equal to 100%. Seems to explain that from initial condition phase to cycle I happened increase equal to 27,2%, from cycle I to cycle II happened increase equal to 45,5%, and from initial condition to cycle II happened increase equal to 72,7%. Thereby,  achievement  of student  learning  in study of mathematics  with matter  line  and  angle  through  approach  of  problem  based  learning  from  finite  initial condition of cycle II happened increase significant.